Peranan Simpan Pinjam Perempuan Dalam PNPM-MP Untuk Kesejahteraan Masyarakat: Studi Kasus di Desa Payaman Kecamatan Plemahan Kabupaten Kediri - Sinollah Sinollah (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2019)
This research was conducted with the aim of finding out how the implementation of the Women's Savings and Loans in the National Program for Empowerment of Rural Independent Communities (PNPM-MP) and the role of the Women's Savings and Loans in the National Program for Empowerment of Independent Rural Communities (PNPM-MP) in improving the welfare of the Payaman Village community. Data collection techniques carried out by interviews, field notes and observations. Data analysis method used in this research is qualitative description analysis, the data obtained are arranged systematically with the good result that can be concluded as clear conception. It also can be provided precise research data about the object of this research. The results showed that SPP in the National Program for Empowerment of Independent Rural Communities was carried out in accordance with the phases in PNPM's PTO (Technical Operational Guidelines). SPP PNPM Mandiri in Rural Areas play a very important role for the Payaman village community, among others, it also can increase business activities, expand employment opportunities and become sources of income especially for women. On the other hand, it also develop the economy of rural communities and become asset that is accessible easily and sustainable. The SPP program carried out in Payaman village has been running in accordance with every steps in the PTO, for this reason there should be guarantees, sanctions or fines applied in each group and it is expected that SPP beneficiaries can be applied to their respective groups so that they should continue to run according to the flow, so the funds can provide benefits in right way and on the target.